Corruption, taxation and the impact on the shadow economy - Daniel Němec; Eva Kotlánová; Igor Kotlán; Zuzana Machová (Economies, 2021)
While assessing the economic impacts of corruption, the corruption-related transmission channels which influence taxation as such have to be duly considered. Taking the example of the Czech Republic, this article aims to evaluate the impacts corruption has on the size of the shadow economy as well as on the individual sources of long-term economic growth, making use of a transmission channel through which corruption affects the tax burden components. Using the method of an extended DSGE model, it confirms the initial assumption that an increase in perceived corruption supports the shadow economy's growth, but at the same time, it demonstrates that corruption and especially its perception has a significantly different effect on two key areas-the capital accumulation and the labour force size. It further identifies another sector of the economy representing taxes which are prone to tax evasion while asserting that corruption has a much more destructive effect on this sector of the economy, offering generalized implications for other postcommunist EU member states in a similar situation.
Keywords: A10; H20; E60; 330; corruption; perceived corruption; DSGE modelling; taxation; tax evasion; shadow economy